Heterogeneous Impacts of Human Activity Intensity on Regional Ecological Security Patterns: The Case of Southwest China - Tao Li; Ling Li; Mingfang Tang; Hongbing Deng (Land)
Intense human activities have significantly altered landscape structure, affected ecosystem services, and threatened ecological security. However, the spatial coupling relationship between regional ecological security patterns (ESPs) and human activity is still unclear. Taking southwest China as the study area, this study firstly assessed ecosystem service importance (ESI) and then identified ecological sources in conjunction with nature reserves. A minimum cumulative resistance model and circuit theory were used to extract ecological corridors and nodes to construct ESPs, and we further analyzed spatial relationships between ESPs and regional human activity intensity factors. Our results showed that ESI had obvious regional differences, and considering diversity and uniqueness of ecosystem functions, it is crucial for constructing ESPs. The ESPs—195 ecological sources, 490 ecological corridors, 212 ecological pinch points, and 17 barrier points—were important priority areas for ecological protection and restoration and will effectively guide differentiated ecosystem management. Intense human activities had significantly differentiated negative impacts on regional ESPs, and balancing regional ecological protection and economic development can achieve a win–win situation. Our research not only provides a new perspective for constructing ESPs but also provides important practical guidance for maintaining ecological security and landscape sustainability.